2009
DOI: 10.1002/ejlt.200800243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thymus haussknechtii and Origanum acutidens essential oils on the stability of cow milk butter

Abstract: The aim of this study was to investigate the effects of different essential oils (from Thymus haussknechtii Velen and Origanum acutidens Hand.-Mazz. Letswaart; endemic species in Turkey) on butter stability. These essential oils were added to butter at two concentrations (0.1 and 0.2 wt-%). The antioxidant activities of the essential oils were compared with control samples (without antioxidant) and containing butylated hydroxytoluene (BHT). All samples were stored at 4 6 1 7C for 90 days and their peroxide val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
6
7
2
Order By: Relevance
“…Control sample showed the highest value (Table 1). Our results were in agreement with Dagdemir et al [8] who indicated that there were no significant differences between Thymus haussknechtii, Origanum acutidens 0.2 and 0.1%, BHT and control butter samples on the 60 th day of storage. Antioxidant activity of N. sativa L., using two TLC screening methods showed that thymoquinone, carvacrol, t-anethole and 4-terpineol demonstrated important radical scavenging property [17] .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Control sample showed the highest value (Table 1). Our results were in agreement with Dagdemir et al [8] who indicated that there were no significant differences between Thymus haussknechtii, Origanum acutidens 0.2 and 0.1%, BHT and control butter samples on the 60 th day of storage. Antioxidant activity of N. sativa L., using two TLC screening methods showed that thymoquinone, carvacrol, t-anethole and 4-terpineol demonstrated important radical scavenging property [17] .…”
Section: Discussionsupporting
confidence: 93%
“…The lowest LAB count was found 5.65±0.07 in NS3 sample (0.2% essential oil) at the end of the storage period (Table 2). This result was in agreement with studies by Ozkan et al [38] and Dagdemir et al [8] who indicated, respectively, that the LAB counts of butter samples containing Saturaja cilicica essential oils and T. haussknechtii and O. acuditens were decreased. It can be concluded that the concentration of essential oil was an important factor of the growth of coliform bacteria.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations